The didactic approach of Paleontology themes in a Midle School in Ponta Grossa, PR, Brazil (Terr@ Plural, 2021)
Paleontology is a fundamental theme for the study and understanding of the origin and evolution of life on earth and is included in documents that govern basic education in Brazilian schools. The city of Ponta Grossa is widely known for its sites with abundant fossiliferous content. Based on the relevance of the theme and the characteristics of the region, this study evaluated the level of knowledge about Paleontology and the preservation of Paleontological Heritage among elementary school students of a public school. We used questionnaires, lectures, exhibitions of fossils from the region, and analysis of the textbooks used by the school with two classes of 7th and 8th grade. In general, the students of the four classes demonstrated a similar level of initial knowledge about the theme, presenting basic conceptualization difficulties and a lack of knowledge about the occurrence of fossils in the region. A lack of approach to the theme in the analyzed textbooks was also verified, which corroborates the low level of knowledge of the students. The activities applied were effective in the appropriation of knowledge, with changes in the level of understanding.
Keywords: Teaching; Textbooks; Paleontological Heritage